Highly effective impact modifier and polymer composition
By developing small-particle, high rubber and highly concentric core-shell impact modifier particles, combined with low surfactant level synthesis methods, the problem of difficult to balance the impact performance and aesthetics of polymer compositions in the prior art is solved, and the effects of high impact strength, low water haze and high gloss are achieved, especially at low loads.
Patent Information
- Application Number
- CN202080024376.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-27
- Filing Date
- 2020-03-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2040-03-24
AI Technical Summary
While improving the impact properties of polymer compositions, it is difficult to maintain high gloss, low temperature haze and high water mist resistance, especially under low loads.
Core-shell impact modifier particles with small particle size and high rubber were developed, and impact modifiers with excellent impact properties and aesthetics were prepared by highly concentric core-shell particles and restricted surfactant use in combination with low surfactant levels of synthesis methods.
It is achieved that a polymer composition with high impact strength is provided while maintaining high gloss and low water haze, and still significantly improves impact performance under low loading.
Smart Images

Figure SMS_30 
Figure SMS_31
Abstract
Description
Technical Field
[0001] The present invention relates to core-shell impact modifier compositions synthesized in a manner having a unique concentric morphology and / or a combination of high rubber loading and low particle size and / or requiring only low surfactant levels, particularly having high T g Nuclear, low T g Inner shell and high T g The incorporation of these impact modifiers into polymer compositions allows new combinations of properties: a combination of high impact strength while maintaining high gloss, or a combination of high impact strength while maintaining low haze in the presence of water at elevated temperatures. These impact modifiers also allow excellent efficiency in use, allowing excellent impact strength to be achieved at low loadings. Background of the Invention
[0003] Polymer articles are often required to have a combination of properties such as excellent impact resistance, excellent aesthetics (e.g., clarity or high gloss for opaque articles), and strong resistance to fogging (often referred to as "low water haze") even in high temperature, high humidity environments. For many polymer materials, a low glass transition temperature (T g ) rubber particles to enhance the impact properties of polymer compositions is well known. In particular, the use of rubber particles composed of low T g The polymer core or shell and high T compatible with the host matrix g Spherical multilayer polymer particles consisting of a polymer shell (so-called "core-shell" impact modifiers) have been used for decades to toughen polymers such as PVC, PLA, PC, acrylic resins, epoxy resins and polyesters. (US3843753, USUS3661994) For some acrylic polymers such as polymethyl methacrylate (PMMA), the use of high T g Nuclear, low T g Rubbery inner shell and high T g The outer shell is beneficial for achieving an optimal level of impact performance (US443103, US4521568, US5270397).
[0004] Unfortunately, the use of core-shell impact-modified particles in polymer compositions, while improving impact properties, has limited toughening potential for brittle polymer matrices such as PMMA. g Significantly improved impact strength can be achieved in acrylic formulations by adding alkyl acrylate comonomers to the matrix and using high rubber loading in the core. However, the use of alkyl acrylate copolymers in the matrix is detrimental to the thermal properties of the composition, such as heat distortion temperature (HDT).
[0005] Furthermore, unfortunately, it has also been demonstrated that the use of core-shell impact-modified particles in polymer compositions, while again improving impact performance, can be detrimental to properties such as gloss, temperature haze (the haze achieved in transparent articles when the temperature is elevated above ambient temperature), and water mist resistance. In US2017 / 0298217A1 and WO2014 / 54543, the use of small particle sizes was demonstrated to improve water mist resistance, but the improvement in impact performance was modest and no improvement was shown in water mist resistance.
[0006] It is highly desirable to develop a core-shell impact modifier that allows excellent impact performance in a brittle matrix such as PMMA while still maintaining very good aesthetics (high clarity or gloss), low temperature haze, and high resistance to water fog. Likewise, it is desirable to develop an efficient impact modifier that can be used at low loadings but still provide excellent impact performance improvements.
[0007] Surprisingly found that, by developing the core-shell impact modifier particles with small particle size and high rubber, can achieve excellent shock properties, while keeping excellent aesthetics.Also found that, by developing highly concentric core-shell particles, improved shock properties, particularly for small particle size.Finally, find that by limiting the use of surfactant in the synthesis of impact modifier particles, particularly for small particle size, can achieve excellent shock strength, while keeping low water mist.By combining all three attributes into one particle, realize efficient core-shell modifier for polymer composition.These compositions are expected to have very strong application value in automobile, building and construction, lighting, optics, electronics, transportation, electricity, signs and display, household appliances, consumer products, coatings, medical treatment, cosmetics, ultraviolet personal care, packaging and additive manufacturing applications. Summary of the invention
[0008] In a first aspect, the present invention is directed to a latex composition comprising core-shell particles, wherein the core-shell particles comprise:
[0009] - 0.5 to 40 wt. %, preferably 1 to 20 wt. %, more preferably 2 to 15 wt. % and most preferably 5 to 10 wt. % of T g >0℃ hard core polymer stage,
[0010] - 10 to 80 wt%, preferably 55 to 80 wt% of T g <0℃ polymer inner shell,
[0011] -5-50 wt%, preferably 10 wt% to 20 wt% T g >0℃ polymer housing,
[0012] and wherein the ratio of the surface area of the emulsifier to the surface area of the core-shell particles is less than 1.5×10 -4 g / m 2 The ratio of emulsifier to surface area of the core-shell particle is based on the as-synthesized core-shell particle without further processing. Examples of further processing include, for example, washing, coagulation and other similar post-polymerization processing methods.
[0013] In a second aspect, the hard core polymer grade of the core-shell particles has at least 50% by weight of monomer units selected from the group consisting of methacrylate units, acrylate units, styrene units, and mixtures thereof.
[0014] In a third aspect of the present invention, the latex composition of any of the above aspects, the polymer inner shell has at least 50% by weight of monomer units selected from the group consisting of alkyl acrylates, diene styrenes, and mixtures thereof.
[0015] In a fourth aspect of the invention, the latex composition of any of the preceding aspects has a polymer shell having at least 50% by weight of monomer units selected from the group consisting of methacrylate units, acrylate units, styrene units, and mixtures thereof.
[0016] In a fifth aspect of the present invention, the latex composition of any one of the preceding aspects, the core-shell particles have a radius of the entire core-shell particle of 100 nm or less.
[0017] In a sixth aspect of the invention, the core-shell particle has a radius of 100 nm or less and consists of:
[0018] - 0.5 to 40 wt. %, preferably 1 to 20 wt. %, more preferably 2 to 15 wt. % and most preferably 5 to 10 wt. % of T g >0℃ hard core polymer grade,
[0019] - 10 to 80 wt%, preferably 55 to 80 wt% of T g <0°C polymer inner shell, and
[0020] -5-50 wt%, preferably 10 wt% to 20 wt% T g >0℃ polymer housing.
[0021] In a seventh aspect of the present invention, the polymer impact-modified composition comprises:
[0022] - 30 to 99% by weight of at least one polymer resin as a matrix, and
[0023] - 1 to 70% by weight of core-shell particles as described in any one of the above aspects.
[0024] In an eighth aspect of the present invention, the composition of the seventh aspect contains a polymer resin which is a thermoplastic resin.
[0025] In a ninth aspect of the present invention, in the composition of aspect 7 or 8, the thermoplastic resin is an acrylic resin.
[0026] In the tenth aspect of the present invention, in the composition of any one of aspects 7 to 9, the concentration of the core-shell particles in the composition is between 10 wt % and 60 wt %, preferably between 20 wt % and 50 wt %.
[0027] In another aspect of the present invention, the polymer resin of the impact-modified composition is a thermosetting resin.
[0028] In other aspects of the invention, the impact modified composition of the foregoing aspects may have any of the following features: an Izod impact strength greater than 1.5 ft-lbs / in; an Izod impact strength greater than 1.0 ft-lbs / in and a tensile modulus greater than 300,000 psi; an Izod impact strength of at least 0.7 ft-lb / in and very low water haze, as indicated by a ΔHaze of less than 1 for a transparent sample or a ΔE of less than 2 for a translucent or opaque sample after immersion in 70°C deionized water for 24 hours and then conditioning at room temperature and 50% RH for >24 hours; an Izod impact strength of at least 0.7 ft-lb / in, and a 60° gloss of greater than 30 after profile extrusion or profile coextrusion of a 250 micron thick part or layer; or an Izod impact strength of at least 0.7 ft-lb / in, and a room temperature haze of less than 2 after immersion in 70°C deionized water for 24 hours and then conditioning at room temperature and 50% RH for >24 hours.
[0029] In another aspect of the invention, the impact modified composition of any of the previous aspects, the matrix and core-shell particles are selected so that the difference in refractive index is within 0.08 units, preferably within 0.05 units, and more preferably within 0.01 units.
[0030] In another aspect of the invention, the impact modified composition of any of the preceding aspects has an Izod impact strength of at least 0.7 ft-lb / in and high clarity as indicated by a TLT greater than 90%.
[0031] In another aspect of the invention, the impact modified composition of any of the preceding aspects has an Izod impact strength of at least 0.7 ft-lb / in, a water haze of less than 10%, and a TLT of greater than 90%.
[0032] Another aspect of the present invention relates to an article made from the impact-modified composition of any of the preceding aspects.
[0033] The article of the aforementioned aspect, wherein the article is formed by melt processing, additive manufacturing technology casting, infusion, wet pressing, resin transfer molding or pultrusion.
[0034] The article of any of the preceding aspects, wherein the article is a multilayer article and at least one layer comprises the impact-modified composition.
[0035] The article of any of the preceding aspects, wherein the article is a fiber reinforced article.
[0036] The article of any of the preceding aspects, wherein the article is a building and construction article, a cover, a railing, a siding, a fence, a door and window profile; an automotive product, an automotive exterior, an automotive interior, an automotive rearview mirror housing, a fender; an electronic product, an earplug, a mobile phone case, a computer case; an energy-related product, a wind energy component, a custom sheet product, a top cover; an optics-related product, a visible film for street signs; a medical product, an IV connection, a Luer connector, a diagnostic component; a sporting product, a shoe sole, a tennis racket, a golf club, a ski; an infrastructure product, a bridge support, a rebar; an outdoor equipment product, a snowmobile component, a recreational vehicle component, a motorboat component, a coating, a medical device, a cosmetic, a UV personal care product, a packaging, and an additive manufacturing component. DETAILED DESCRIPTION
[0037] The present invention relates to a core-shell impact modifier composition and a polymer composition comprising the core-shell impact modifier.
[0038] Unless otherwise indicated, all percentages used herein are by weight and all molecular weights are weight average molecular weights as determined by gel permeation. All references listed are incorporated herein by reference.
[0039] The invention will be generally described and will also include a core-shell / acrylic polymer system as a model system. One of ordinary skill in the art will recognize that other polymer matrices may be used with comparable results based on the following description and examples.
[0040] Composition
[0041] Core-Shell Impact Modifiers
[0042] The impact modifier of the present invention is a multi-stage, sequentially produced polymer with a core-shell particle structure. The core-shell impact modifier comprises at least three layers (hard core / inner elastomer shell / outer hard shell, referred to as "hard core, core-shell particles") or any higher number of layers, such as a soft seed core surrounded by a hard core / elastomer intermediate shell / second different elastomer layer / and one or more high Tg outer shell layers. Other similar multilayer structures are known in the art.
[0043] In a preferred embodiment, the presence of a hard core layer provides an ideal balance of good impact strength, high modulus and excellent UV resistance, which cannot be achieved using a core / shell modifier with a soft core layer. The core layer is defined herein as a polymer layer having at least two polymer layers on its exterior. It does not have to be the innermost layer of the particle. The hard core layer (T g >0℃, preferably T g >20℃) is usually a single composition polymer, but may also include a small amount of low T g A combination of seeds on which a hard core layer is formed. For example, a small 5% rubber core seed dispersed into a hard inner layer would be included in the present invention as a hard core layer as long as the combination exhibits a hard core high T g The hard core layer can be selected from the g Any monomer combination required. Preferably, the hard core layer is mainly composed of methacrylate units, acrylate units, styrene units or mixtures thereof. The methacrylate units include, but are not limited to, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, pentadecyl methacrylate, dodecyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate and 2-methoxyethyl methacrylate. Acrylate units include, but are not limited to, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, n-hexyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, pentadecyl acrylate, dodecyl acrylate, isobornyl acrylate, phenyl acrylate, benzyl acrylate, phenoxyethyl acrylate, 2-hydroxyethyl acrylate, and 2-methoxyethyl acrylate. Preferably, the acrylate units are selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, and octyl acrylate. Styrene units include styrene and its derivatives, such as, but not limited to, α-methylstyrene and p-methylstyrene. In one embodiment, the hard core layer is all acrylic. In another embodiment, the hard core layer is an acrylic with <30% styrene monomer units.
[0044] At least one or more intermediate inner shell layers are elastomeric, having a T of less than 0°C and preferably less than -20°C. g. Preferred elastomers include polymers and copolymers of alkyl acrylates, dienes, styrenes and mixtures thereof. Preferably, the soft intermediate layer consists primarily of acrylate units. Acrylate units that can be used to form the soft block include, but are not limited to, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, n-hexyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, pentadecyl acrylate, dodecyl acrylate, isobornyl acrylate, phenyl acrylate, benzyl acrylate, phenoxyethyl acrylate, 2-hydroxyethyl acrylate and 2-methoxyethyl acrylate. Preferably, the acrylate units are selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate and octyl acrylate. Useful dienes include, but are not limited to, isoprene and butadiene. Useful styrenes include, but are not limited to, α-methylstyrene and p-methylstyrene. In a preferred embodiment, the acrylate units account for >75% of the inner shell layer of one or more elastomers. The total amount of the elastomeric layer in the impact modifier is preferably 30-90 wt%, more preferably 40-85 wt%, and most preferably 55-80 wt%, based on the total weight of the impact modifier particle.
[0045] The outer hard shell layer can be made of one or more shell layers, with T g >0℃, more preferably T g >20°C, preferably selected from the list above for the hard core. The outer shell layer can be the same or different composition as the hard core layer. As described in US7195820B2, a certain degree of functionalization may be included in the shell to help compatibility with the polymer matrix. Hydrophilic monomers may also be included in the shell to improve shell coverage or improve anti-adhesion. Examples of useful hydrophilic monomers include, but are not limited to, hydroxyalkyl (meth) acrylates, (meth) acrylic acid, (meth) acrylamide, (meth) acrylic amine, polymerizable surfactants and macromonomers containing hydrophilic parts.
[0046] In one aspect of the invention, the core-shell polymer is a three-stage composition, wherein the stages are present in the following ranges: 0.5 wt % to 40 wt %, preferably 1 wt % to 20 wt %, more preferably 2-15 wt % and even 5-10 wt % of the first stage hard core layer; 10 wt % to 80 wt %, preferably 55 wt % to 80 wt % of the second elastomeric inner shell stage; and 5 % to 50 %, preferably 10 % to 20 % of the outer shell stage, all percentages based on the total weight of the three-stage polymer particles. The core-shell polymer particles will have a radius of <200 nm, more preferably <100 nm. When the core-shell particles are added to the polymer composition, the small particle size is conducive to maintaining excellent aesthetic properties, such as transparency or high gloss.
[0047] In another aspect of the invention, the core-shell polymer is synthesized in a manner that produces concentric round particles (particles resembling a perfect bull's eye). This concentricity and roundness is found to be beneficial in maximizing impact performance when utilized in a polymer composition.
[0048] Core-shell polymers can be produced by any known technique for preparing multi-stage, sequentially produced polymers, for example, by emulsion polymerization of a monomer mixture of a subsequent stage in the presence of a previously formed polymer product. In this specification, the term "sequential emulsion polymerization" or "sequential emulsion production" refers to polymers prepared in an aqueous dispersion or emulsion and in which successive monomer feeds are polymerized on or in the presence of a preformed latex prepared by polymerization of previous monomer feeds and stages. In this type of polymerization, the subsequent stage is connected and closely related to the previous stage.
[0049] In a preferred embodiment, the impact modifier is prepared by sequential emulsion polymerization. As known in the art, in this type of polymerization, emulsifiers are usually used to allow monomers to be fed to the stabilization / transmission of the growing core-shell particles and the stabilization of the core-shell particles themselves in aqueous media. Emulsifiers are defined as any organic or inorganic molecule having both hydrophobic and hydrophilic components in its structure. Any known surfactant can be used as an emulsifier, no matter it is anionic, nonionic or even cationic. Especially, emulsifiers can be selected from anionic emulsifiers, such as sodium salts or potassium salts of fatty acids, particularly sodium laurate, sodium stearate, sodium palmitate, sodium oleate, sodium or potassium and mixed sulfates of fatty alcohols, particularly sodium lauryl sulfate, sodium salts or potassium salts of sulfosuccinates, sodium salts or potassium salts of alkyl aryl sulfonic acids, particularly sodium dodecylbenzene sulfonate, and sodium salts or potassium salts of fatty monoglyceride monosulfonates, or nonionic surfactants, such as the reaction product of ethylene oxide and alkylphenols or fatty alcohols, alkylphenols. Mixtures of these surfactants can also be used if desired.
[0050] In a more preferred embodiment, the particles are synthesized in an emulsion such that the ratio of the weight of the emulsifier to the surface area of the core-shell particles is less than 1.5×10 -4 g / m 2 And preferably less than 9×10 -5 g / m 2The ratio is the ratio that would exist in the emulsion or after the recovery process if no specific steps were utilized to remove the emulsifier. Steps to remove the emulsifier include, but are not limited to, latex coagulation, latex dialysis, or washing of separated particles; these methods generally improve water haze performance beyond the requirements of the present invention, but introduce additional manufacturing steps and increase costs. Spray drying is a method known in the art to effectively recover core-shell particles at low cost without the need for additional expensive steps to remove the emulsifier. When the core-shell particles are used in a polymer composition, having a low emulsifier level in the particles recovered by spray drying is beneficial in maintaining a low water haze.
[0051] In one aspect of the invention, wherein the impact modifier is prepared by sequential emulsion polymerization, the aqueous reaction mixture obtained at the end of the final emulsion polymerization stage, which consists of an aqueous emulsion of the polymer according to the present invention, then treated to recover the polymer therefrom, in many cases in powder form. Spray drying is a particularly preferred technology. An effective but more costly technology is coagulation, wherein the emulsion is coagulated by contacting with a saline solution (CaCl or AlCl) or a solution acidified with concentrated sulfuric acid, according to the emulsifier used, and then the solid product produced by coagulation is separated by filtration, and then the solid product is washed and dried to obtain a graft copolymer in powder form. The polymer contained in the emulsion can also be recovered by using rotary drum drying, freeze drying or other means known in the art. In any of these processes, additives such as talcum, calcium carbonate or silicon dioxide can be used to help process the powder. Hard particles can be used in combination with the core-shell particles of the present invention to further improve anti-adhesion and processing properties.
[0052] The impact modifier particles of the present invention can be intimately combined with polymers, organic or inorganic dispersing aids, anti-caking and / or other processing aids or other impact modifiers as commonly practiced by the industry during spray drying or coagulation recovery processes. This process forms impact modifier composite particles in which the core-shell impact modifier particles are intimately combined with polymers, organic or inorganic additives or processing aids. The core-shell impact modifier composite particles can be produced and subsequently recovered into powder form by means known in the art, including but not limited to co-spray drying as separate streams entering a spray dryer; blending the core-shell particles and processing aid as a dispersion and spray drying the mixture; co-coagulation; co-freeze drying; applying a dispersion or solution of the processing aid to the core-shell powder followed by drying; physical blending of the impact modifier and processing aid powders, which increases the homogeneity of the powder form and results in more uniform blending into the matrix during melt blending; and physical blending followed by weak melt blending of the impact modifier and processing aid powders, allowing the particles to soften and adhere without complete melting.
[0053] The impact modifier particles are present in the final impact modified polymer composition at a level of 5 to 80 wt%, preferably 10 to 60 wt% and more preferably 20 to 50 wt%, based on the total composition.
[0054] Polymer composition
[0055] The resin used as the matrix polymer in the composition of the present invention can be any thermoplastic or thermosetting resin. Particularly preferred thermoplastics include, but are not limited to, acrylic polymers, styrene polymers, polyolefins, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyvinyl chloride (PVC), polycarbonate (PC), thermoplastic polyurethane (PU), polylactic acid (PLA), thermoplastic fluoropolymers, polyamides or mixtures thereof. Particularly preferred thermosetting polymers include, but are not limited to, epoxy resins, unsaturated polyester resins, vinyl ester resins, thermosetting polyurethanes, urea-formaldehyde, melamine formaldehyde, UV-curable and thermosetting acrylic resins.
[0056] As used herein, styrenic polymers include, but are not limited to, polystyrene, high impact polystyrene (HIPS), acrylonitrile-butadiene-styrene (ABS) copolymers, acrylonitrile-styrene-acrylate (ASA) copolymers, styrene acrylonitrile (SAN) copolymers, methacrylate-acrylonitrile-butadiene-styrene (MABS) copolymers, styrene-butadiene copolymers (SB), styrene-butadiene-styrene block (SBS) copolymers and partially or fully hydrogenated derivatives thereof, styrene-isoprene copolymers styrene-isoprene-styrene (SIS) block copolymers and partially or fully hydrogenated derivatives thereof, styrene-(meth)acrylate copolymers such as styrene-methyl methacrylate copolymers (S / MMA), and mixtures thereof. A preferred styrenic polymer is ASA.
[0057] As used herein, acrylic polymers include but are not limited to homopolymers, copolymers and terpolymers comprising alkyl methacrylate. The alkyl methacrylate monomer is preferably methyl methacrylate, which can account for 51% to 100% by weight of the monomer mixture, preferably greater than 60% by weight, more preferably greater than 75% by weight, and most preferably greater than 85% by weight. The remaining monomers for forming the polymer are selected from other acrylates, methacrylates and / or other vinyl monomers. Other methacrylates, acrylates and vinyl monomers that can be used in the monomer mixture include but are not limited to methyl acrylate, ethyl acrylate and ethyl methacrylate, butyl acrylate and butyl methacrylate, isooctyl methacrylate and isooctyl methacrylate, lauryl acrylate and lauryl methacrylate, stearyl acrylate and stearyl methacrylate, isobornyl acrylate and isobornyl methacrylate, methoxyethyl acrylate and methoxyethyl methacrylate, 2-ethoxyethyl acrylate and 2-ethoxyethyl methacrylate, dimethylaminoethyl acrylate and dimethylaminoethyl methacrylate monomers, styrene and derivatives thereof. Alkyl (meth) acrylic acid such as (meth) acrylic acid and acrylic acid can be used in the monomer mixture. Small amounts of multifunctional monomers may also be used as crosslinking agents. A preferred acrylic polymer is a copolymer of methyl methacrylate and 2-16% of one or more C1-4 acrylic esters.
[0058] The thermoplastic or thermosetting polymers of the present invention can be manufactured by any means known in the art, including emulsion polymerization, bulk polymerization, solution polymerization, and suspension polymerization. In one embodiment, the weight average molecular weight of the polymer matrix is 50,000 to 5,000,000 g / mol, and preferably 75,000 to 150,000 g / mol, as measured by gel permeation chromatography (GPC). The molecular weight distribution of the polymer matrix can be unimodal, or multimodal with a polydispersity index greater than 1.5.
[0059] In one embodiment, the composition of the polymer matrix and the core-shell particle are selected such that the refractive indices are within 0.008 units, preferably within 0.005 units and more preferably within 0.001 units, thereby allowing for a clear formulation.
[0060] In another embodiment, dyes or pigments are added to the composition to allow for translucent or opaque materials. The level of pigment or dye in the composition is preferably from 0.2% to 25% by weight, preferably from 0.5% to 20% by weight, and most preferably from 1% to 5% by weight, based on the total composition. The addition of dyes or pigments can produce a transparent article with a haze level of less than 10% and preferably less than 3%; a translucent article with a haze level of 10% to 35%, preferably 15% to 25%; or an opaque article.
[0061] Useful dyes and pigments of the present invention include, but are not limited to, nanocarbon materials such as graphite or carbon nanotubes, cadmium zinc sulfide, CI Pigment Yellow 35, (CAS Reg. No. 8048-07-5, Reach No. 01-2119981639-18-0001), cadmium sulfoselenide orange, CI Pigment Orange 20, (CAS Reg. No. 12656-57-4, Reach No. 01-2119981636-24-0001), cadmium sulfoselenide red (CI Pigment Red 108, CAS Reg. No. 58339-34-7, Reach No. 01-2119981636-24-0001), carbon black (PBlk-7), TiO2 (PW-6), BaSO4 (PW-21 and PW-22), CaCO3 (PW-18), PbCO3, Pb(OH)2, (PW1), Yellow 6G, M Yellow 3G, Huang G, Huang E2R, Huang RN, Orange 3G, Orange R, Red E2G, Red A, Red EG, Red G, Red H, Red B, Red 5B, Red and purple, Purple 3R, Purple B, Purple 3B, Blue 3R, Blue RR, M Blue 2B, Green 5B, Green G, Fluorescent Yel and
[0062] Other additives:
[0063] The composition may optionally contain one or more typical additives for polymer compositions used in generally effective amounts, including but not limited to other impact modifiers (core-shell and linear block copolymers), stabilizers, plasticizers, fillers, additives to improve scratch and / or mar resistance, colorants, pigments, antioxidants, antistatic agents, surfactants, toners, refractive index matching additives, additives with specific light diffraction, light absorption or light reflection properties, dispersion aids, radiation stabilizers such as poly (ethylene glycol), poly (propylene glycol), butyl lactate, and carboxylic acids such as lactic acid, oxalic acid and acetic acid, light modification additives, such as polymeric or inorganic spherical particles with a particle size between 0.5 microns and 1,000 microns. The amount of additives included in the polymer composition may vary from about 0% to about 70% of the combined weight of the polymer, inorganic mineral oxide and additives. Amounts of about 0.5% to about 45%, preferably about 5% to about 40%, are generally included. The additives may be added to the composition before addition to the extruder, or may be partially added to the molten composition by the extruder.
[0064] Processing
[0065] Synthesis process of core-shell composite impact modifier
[0066] The core / shell polymers of the present invention are preferably synthesized by emulsion free radical polymerization. A general procedure for producing four-stage core-shell polymer particles will be described. Those skilled in the art will be able to modify this procedure to form other core-shell particles that can be used as impact modifiers.
[0067] In the first stage (hard core layer), an emulsion is prepared, which contains 1 to 10 parts of water, 0.001 to 0.03 parts of emulsifiers, a portion of a (meth)acrylate monomer mixture and at least one multifunctional crosslinking agent per part by weight of the monomer to be polymerized. The reaction mixture thus formed is stirred and maintained in a temperature range of 45°C to 85°C, and preferably in a temperature range of 60-80°C. Then 0.0001 to 0.005 parts of a catalyst that generates free radicals are added together with an equal part of an activator compound that increases the free radical flux, and the reaction mixture thus formed is maintained at a temperature between, for example, ambient temperature and 100°C and stirred for a period of time sufficient to obtain almost complete conversion of the monomers. Then, further alkyl acrylate monomers and grafting agents are added to the phase thus obtained, and at the same time, 0.0001 to 0.005 parts of a catalyst that generates free radicals are then added simultaneously until the target particle size is reached.
[0068] In the second stage, to the core are grafted selected monomers which will form a polymer (inner shell) with a Tg<0°C. To this end, an appropriate amount of the monomer mixture is added to the reaction mixture resulting from the first stage so as to obtain a graft copolymer containing the desired content of grafted chains, and, where appropriate, additional amounts of emulsifier and free radical catalyst also within the range defined above, and the mixture thus formed is maintained at a temperature above the above range, while stirring, until an almost complete conversion of the grafted monomers is obtained. As mentioned above, any known surfactant may be used as an emulsifier, whether anionic, nonionic or even cationic. In particular, the emulsifier can be selected from anionic emulsifiers, such as sodium or potassium salts of fatty acids, in particular sodium laurate, sodium stearate, sodium palmitate, sodium oleate, sodium or potassium mixed sulfates with fatty alcohols, in particular sodium lauryl sulfate, sodium or potassium salts of sulfosuccinates, sodium or potassium salts of alkylarylsulfonic acids, in particular sodium dodecylbenzenesulfonate, and sodium or potassium salts of fatty monoglyceride monosulfonates, or nonionic surfactants, such as reaction products of ethylene oxide with alkylphenols or fatty alcohols, alkylphenols. If desired, mixtures of these surfactants can also be used. In one embodiment, the emulsion can be prepared in a semi-continuous process, preferably at a reaction temperature of 60-90° C. and preferably 75° C. to 85° C.
[0069] In the third stage, the elastomeric shell is grafted with selected monomers which will form a polymer (outer shell) with a Tg>0°C. To this end, an appropriate amount of the monomer mixture is added to the reaction mixture resulting from the second stage in order to obtain a graft copolymer containing the desired content of grafted chains, and, where appropriate, additional amounts of emulsifier and free radical catalyst also within the range defined above, and the mixture thus formed is maintained at a temperature within the range of the second stage under stirring until an almost complete conversion of the grafted monomers is obtained. As mentioned above, any of the known surfactants can be used as emulsifiers, whether anionic, nonionic or even cationic. In one embodiment, the emulsion can be prepared in a semi-continuous process, preferably at a reaction temperature of 60-90°C and preferably 75°C to 85°C.
[0070] In the fourth stage, the process of the third stage is repeated so that the shell thickness will increase and the resulting latex can be separated into powder by spray drying.
[0071] In general, the preferred catalysts that can be used in all stages are compounds that generate free radicals under the temperature conditions selected for polymerization. These compounds can be especially peroxide compounds, such as hydrogen peroxide, alkali metal persulfates and especially sodium persulfate or potassium persulfate, ammonium persulfate; percarbonate, peracetate, perborate, peroxide such as benzoyl peroxide or lauroyl peroxide, or hydroperoxide such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, tert-amyl or tert-butyl hydroperoxide. However, it is preferred to use in the nuclear grade a redox catalytic system formed by a combination of non-ionic peroxide compounds such as tert-butyl hydroperoxide as described above and a reducing agent, in particular such as alkali metal sulfites, alkali metal bisulfites, sodium formaldehyde sulfoxylate (NaHSO.Sub.2.HCHO), ascorbic acid, glucose, and in particular those of the catalytic system having water solubility, such as tert-butyl hydroperoxide / bruggolite ff7, or diisopropylbenzene hydroperoxide / sodium formaldehyde sulfoxylate. It is also possible to add to the polymerization mixture of one and / or the other stages chain-limiting compounds, and in particular mercaptans, such as dodecyl mercaptan, isobutyl mercaptan, octyl mercaptan, dithiooctane or isooctyl mercaptopropionate, for the purpose of controlling the molecular mass of the core and / or of the chains grafted onto the core, or compounds such as phosphates, for the purpose of controlling the ionic strength of the polymerization mixture.
[0072] Process for incorporating core-shell particles of core-shell composite particles into polymer compositions
[0073] The polymer matrix and core-shell particles or core-shell composite particles can be combined in several different ways to provide a well-dispersed impact modifier in the composition. The preferred method of the thermoplastic matrix includes a melt processing step. A particularly preferred method is to mix the thermoplastic matrix with the core-shell particles in an extruder such as a twin screw extruder. The key is to obtain a well-dispersed core-shell particle.
[0074] Other ways of combining a thermoplastic matrix with core-shell particles or core-shell composite particles include, but are not limited to: 1.) blending of a thermoplastic polymer matrix with core-shell particles, wherein both materials are in a colloidal state. The latex blend can be used as is or subsequently recovered as a solid via methods such as spray drying or coagulation; 2.) incorporating the core-shell particles directly into a liquid resin (wherein the liquid resin prior to core-shell addition comprises at least 25% matrix monomers) followed by polymerization (e.g., unit casting of MMA, polymerization of liquid composite resins, or additive manufacturing techniques such as stereolithography (SLA)); 3.) solvent casting of particles and dissolved matrix polymers; 4.) powder blending followed by melt processing, such as, but not limited to, extrusion, coextrusion, injection molding, compression molding, or thermoforming; 5.) powder blending followed by additive manufacturing techniques such as selective laser sintering (SLS).
[0075] For thermosetting resins, a preferred embodiment is to physically mix core-shell particles or core-shell composite particles into liquid resin before complete curing occurs. Thermosetting core-shell mixtures can then be processed via casting or UV curing or additive manufacturing techniques (such as SLA) to form thermosetting products or adhesives. Thermosetting core-shell mixtures can also be processed via techniques such as infusion, resin transfer molding or pultrusion to form fiber-reinforced composite structures. Other methods may include but are not limited to powder blending, such as incorporating core-shell particles into solid epoxy resin coatings, or then performing additive manufacturing techniques such as SLS.
[0076] Products
[0077] For thermoplastic matrices, the articles and plates tested are preferably formed by thermal processing. Useful thermal processing methods include, but are not limited to, injection molding, extrusion and coextrusion, film extrusion, blow molding, lamination, extrusion lamination, rotational molding, infusion, pultrusion, compression molding, and fused deposition molding. For liquid thermoplastic resins, techniques such as casting, curing on an adhesive, or SLA may be utilized, while for fiber-reinforced thermoplastic articles, processing techniques such as infusion, resin transfer molding, or pultrusion may be utilized. Additive manufacturing techniques such as fused deposition modeling (FDM) or laser sintering may also be utilized.
[0078] For thermoset articles, processes such as casting, adhesive curing, infusion, resin transfer molding, wet compression molding, pultrusion, spraying, and layup can be used to form articles and panels for testing. Additive manufacturing techniques such as SLA or SLS can be used.
[0079] Other additives and optional pigments and dyes may be dry blended into the composition prior to thermal processing into the final article. In the case of some additives such as pigments or dyes, a masterbatch containing a concentrate may be used.
[0080] The present invention also contemplates multi-layer articles. The composition of the present invention may be used on the outside, inside or any intermediate layer. Multi-layer articles may be two or more layers, which may include adhesives and / or tie layers.
[0081] The present invention also contemplates fiber-reinforced articles. Useful fibers may include, but are not limited to, glass, carbon, or natural fibers.
[0082] performance
[0083] The polymer compositions of the present invention, when processed to form articles or test specimens, provide a unique combination of impact resistance, aesthetics, and low water haze that is useful in several applications.
[0084] In a preferred embodiment, the article has high impact resistance. The polymer composition achieves an impact resistance of >1.5 ft-lbs / in when measured by notched Izod (ASTM D256).
[0085] In another preferred embodiment, the article has a high level of impact strength while maintaining a high modulus due to the need to use a lower loading of a high efficiency impact modifier. The polymer composition achieves an impact resistance of >1 ft-lbs / in when measured by notched Izod (ASTM D256), yet maintains a tensile modulus of >300,000 psi (ASTM D638).
[0086] In a preferred embodiment, the opaque / translucent articles of the present invention have at least moderate levels of impact strength (notched Izod>0.7 ft-lbs / in according to ASTM 256), but maintain high gloss even after profile extrusion. The 60° gloss after profile extrusion or profile coextrusion of a 250 micron thick part or layer is>30 as measured by a Byk-Gardner Microgloss Meter.
[0087] In a preferred embodiment, the opaque / translucent articles of the present invention have at least a moderate level of impact strength (notched Izod>0.7 ft-lbs / in according to ASTM 256), but the water haze of the material is also very low, as indicated by a ΔE color value of less than 2.0 and preferably less than 1.0 after the specimen is exposed to 70°C for 24 hours (as measured by CIE L*a*b* on an X-Rite Color I7 spectrophotometer).
[0088] In a particularly preferred embodiment, the opaque / translucent articles of the present invention have at least a moderate level of impact strength (notched Izod>0.7 ft-lbs / in according to ASTM 256), a high level of gloss (60° gloss after profile extrusion or profile coextrusion of a 250 micron thick part or layer>45, as measured by a Byk-Gardner microgloss meter), and the water haze of the material is also very low, as indicated by a ΔE color value (as measured by CIE L*a*b* on an X-Rite Color I7 spectrophotometer) of <2 after the sample is exposed to 70°C for 24 hours.
[0089] In a preferred embodiment, the transparent articles of the present invention have at least moderate levels of impact strength (notched Izod>0.7 ft-lbs / in according to ASTM 256), yet maintain high clarity, as measured by total light transmittance (TLT)>90% as measured by ASTM D1003.
[0090] In a preferred embodiment, the transparent articles of the present invention have at least a moderate level of impact strength (notched Izod>0.7 ft-lbs / in according to ASTM 256), but the water haze of the material is also very low, as indicated by a haze change of <5 units (measured according to ASTM D1003) after immersion in 70°C deionized water for 24 hours and then conditioning at 50% RH at room temperature for >24 hours.
[0091] In a particularly preferred embodiment, the transparent articles of the present invention have at least a moderate level of impact strength (notched Izod>0.7 ft-lbs / in according to ASTM 256) and high clarity (TLT>90% as measured according to ASTM D1003), and the material also has very low water haze, as indicated by a haze change of <2 units (measured according to ASTM D1003) after immersion in 70°C deionized water for 24 hours and then conditioning at 50% RH at room temperature for >24 hours.
[0092] The present invention also contemplates low temperature haze of the polymer composition due to the preferred small particle size of the present invention. The haze is expected to change by <20% when the temperature is increased from ambient to 80°C (measured according to ASTM D1003).
[0093] use
[0094] The compositions of the present invention can be used to form high impact strength, excellent aesthetics and low water haze articles for the following applications, including but not limited to: building and construction (such as decking, railings, siding, fences and door and window profiles); automotive applications (such as exteriors, interiors, rearview mirror housings, fenders); electronics (such as earplugs, mobile phone cases, computer cases); energy applications (such as wind energy) custom sheet applications, especially as top cover materials; optical applications (high-visibility films for street signs); medical (IV connections such as Luer connectors, diagnostic components), sporting goods (such as soles, tennis rackets, golf clubs, skis), infrastructure (such as bridges, rebar), outdoor equipment (such as snowmobiles, recreational vehicles, motorboats) and any type of additive manufacturing application.
[0095] In this specification, the embodiments have been described in a manner that enables a clear and concise description to be written, but it is intended and will be understood that the embodiments can be combined or separated in various ways without departing from the present invention. For example, it should be understood that all preferred features described herein are applicable to all aspects of the present invention described herein.
[0096] Example:
[0097] Test method:
[0098] The specimens used for physical and optical testing were injection molded to a thickness of 3.18 ± 0.05 mm, with other dimensions specified in the ASTM standards.
[0099] A. Tg: glass transition temperature (Tg), measured by DSC (Differential Scanning Calorimetry) according to Standard ISO 11357-2 (2013) and Standard ISO 11357-3 (2013), according to the following protocol:
[0100] 1: Equilibrate at 20.00℃
[0101] 2: Cool to -50.00℃ at a rate of 10.00℃ / min
[0102] 3: Maintain this temperature for 5.00 minutes
[0103] 4: Heat to 250.00℃ at a rate of 20.00℃ / min
[0104] 5: Maintain this temperature for 5.00 minutes
[0105] 6: Cool to -50.00℃ at a rate of 10.00℃ / min
[0106] 7: Maintain this temperature for 5.00 minutes
[0107] 8: Heat to 250.00℃ at a rate of 20.00℃ / min
[0108] B. Ratio of emulsifier to surface area.
[0109] The ratio of emulsifier to surface area is a calculated value. Use NICOMP380 dynamic light scattering instrument to measure volume average product size and average particle number by light scattering on latex. By weighing the aluminum pan, adding the latex polymer and weighing, then evaporating water in an oven to obtain the polymer solid as mass percentage to determine polymer solids. Calculate the surface area of the particles based on the volume average radius determined by light scattering. Assume that the amount of the emulsifier added to the latex is all present on the particle surface. Polymer density is obtained by obtaining the mass of solid polymer material and divided by volume. By using average particle number and volume average particle size, calculating surface area, calculating density and polymer concentration and polymer density, the ratio of emulsifier to surface area can be calculated.
[0110] C. Water Haze. It is the measured difference between the haze of a sample injection molded and conditioned at room temperature and humidity (23°C, 50% relative humidity, RH) and the haze of a sample immersed in 70°C deionized water for 24 hours and then conditioned at room temperature and 50% RH (as measured using BYK HazeGard Plus according to ASTM method D1003 for samples with a total light transmittance greater than 50%). Alternatively, for opaque samples, the difference in final color from initial color (ΔE) may be used instead of (ΔHaze) as previously described.
[0111] D. Gloss: The surface gloss was measured using a BYK Spectro-Guide at a measuring angle of 60 degrees.
[0112] E. Notched Izod impact strength measured according to ASTM D256
[0113] Abbreviations used in the examples:
[0114] MMA = Methyl Methacrylate
[0115] EA = Ethyl Acrylate
[0116] BA = Butyl acrylate
[0117] MA = Methyl acrylate
[0118] Sty=Styrene
[0119] ALMA=Allyl methacrylate
[0120] GMAA = Glacial Methacrylic Acid
[0121] KDDBS = Potassium dodecylbenzene sulfonate
[0122] Example 1
[0123] This example illustrates the preparation of a multi-stage, sequentially produced polymer of the composition.
[0124] The ratio of the three levels is 10 / / 75 / / 15
[0125] The three levels are composed of
[0126] Level 1: 79 / 20 / 1MMA / BA / ALMA
[0127] Level 2: 82 / 17 / 1BA / Sty / ALMA
[0128] Level 3: 100MMA
[0129] The monomer feed consisting of stage 1 is emulsified in deionized water using KDDBS. The emulsion is heated to 50-70°C and initiated with a 1:1 weight ratio of tert-butyl hydroperoxide to bruggolite(R) FF7 reducing agent to obtain a suitable polymerization rate. The temperature is raised to at least 80°C and after almost complete conversion, potassium carbonate is added to adjust the pH of stages 2 and 3. The stage 2 mixture is gradually fed with a controlled amount of KDDBS to limit the formation of new particles and maintain latex stability. Potassium persulfate is added simultaneously with the stage 2 mixture to control the polymerization rate, residual salt content and pH level. After addition, the latex is cured until the remaining monomer is <1%. A limited amount of surfactant is gradually added to the stage 3 monomer mixture to control particle growth. After addition, the latex is cured until the remaining monomer is <0.1%. The polymer is isolated by coagulation, freeze drying or spray drying.
[0130] Example 2
[0131] This polymer was prepared in a similar manner to Example 1, except that it had a different step ratio:
[0132] The ratio of the three levels is 2 / / 75 / / 23
[0133] The composition of the stage is
[0134] Level 1: 8 / 90 / 2MMA / Sty / ALMA
[0135] Level 2: 85 / 14 / 1.0BA / Sty / ALMA
[0136] Level 3: 100MMA
[0137] Example 3
[0138] This polymer was prepared in a similar manner to Example 1, except that it had a different step ratio:
[0139] The ratio of the three levels is 6 / / 75 / / 19
[0140] The composition of the stage is
[0141] Level 1: 8 / 90 / 2MMA / Sty / ALMA
[0142] Level 2: 84 / 15 / 1.0BA / Sty / ALMA
[0143] Level 3: 99 / 1MMA / GMAA
[0144] Example 4
[0145] This polymer was prepared in a similar manner to Example 1, except that it had a different step ratio:
[0146] The ratio of the three levels is 7 / / 75 / / 18
[0147] The composition of the stage is
[0148] Level 1: 80 / 10 / 9.8 / 0.2MMA / Sty / BA / ALMA
[0149] Level 2: 84 / 15 / 1BA / Sty / ALMA
[0150] Level 3: 99 / 1MMA / BA
[0151] Examples 5 and 6 (Comparative)
[0152] This example illustrates the preparation of multi-stage, sequentially produced polymers of given composition using prior art methods targeting radii of 80 nm and 150 nm, respectively.
[0153] The ratio of the three levels is 15 / / 65 / / 20
[0154] The three levels are composed of
[0155] Level 1: 74.8 / 25 / 0.2MMA / EA / ALMA
[0156] Level 2: 83.5 / 15.5 / 1.0BA / Sty / ALMA
[0157] Level 3: 95 / 5MMA / EA
[0158] A monomer feed consisting of 34% of stage 1 is emulsified in water using KDDBS as an emulsifier and potassium carbonate to control pH, and polymerized using potassium persulfate at elevated temperature. The remainder of stage 1 is then added to the preformed polymer emulsion and polymerized using potassium persulfate at elevated temperature, controlling the amount of soap added to prevent the formation of a large number of new particles. Stage 2 monomers are then added and polymerized using potassium persulfate at elevated temperature, controlling the amount of soap added to prevent the formation of a large number of new particles. Stage 3 monomers are then polymerized using potassium persulfate at elevated temperature, and again controlling the amount of soap added to prevent the formation of a large number of new particles. The polymer is isolated by coagulation, freeze drying, or spray drying.
[0159] The ratio of the three levels is 35 / / 45 / / 20
[0160] The three levels are composed of
[0161] Level 1: 95.8 / 0.4 / 0.2MMA / EA / ALMA
[0162] Level 2: 80 / 18 / 2.0BA / Sty / ALMA
[0163] Level 3: 96 / 4MMA / EA
[0164] Embodiment 7-13
[0165] The polymers of Examples 1-6 were blended in an extruder with the listed amounts of acrylic copolymer matrix.
[0166]
[0167]
[0168] Examples 7-13 were formed into 1 / 8" plaques and 1 / 8" x 0.5" x 2.5" Izod rods. The energy per unit length of notch was measured on a Ceast Izod tester according to ASTM D256.
[0169] This table clearly shows the advantage of dispersing an optimized elastomeric polymer in an acrylic copolymer matrix containing lower levels of surfactant. Example 7 exhibits 2.67 times higher impact resistance and 8.1 units less haze than Example 11 after immersion at 70°C for 24 hours; while maintaining optical properties such as TLT and haze. It also illustrates the advantage of a mixed initiator system in a core-shell synthesis process. Example 8 shows that an impact resistance of 2.65 ft-lb / in can be achieved with little impact on optical properties. Example 9 shows that a tensile modulus in excess of 300,000 psi can be achieved while having an impact resistance of 1.19 ft-lb / in.
[0170] Examples 14-15 (profile extrusion)
[0171] Example 14 and Example 15 are composed of the materials from Example 10 and Example 13, respectively, coextruded on PVC by profile extrusion, wherein the cover layer thickness is 200-250 microns. The PVC thickness is 1160-1270 microns. The GVHIT impact strength of the composite material is then tested according to ASTM-D4226-00.
[0172] <![CDATA[ GVHIT ]]> <![CDATA[ Gloss at 60° ]]> Embodiment 14 1.3in-lb. / mil 45±3 Embodiment 15 1.1in-lb. / mil 15±3
[0173] The advantages of materials such as Example 14 are apparent when compared to more traditional acrylics such as Example 15. Example 15 does not meet the gloss requirements achieved by the present invention.
Claims
1. A core-shell particle having a radius of 100 nm or less, wherein the core-shell particle comprises: a. 0.5 to 10 wt% T g >0℃ hard core polymer grade, b. 10 to 80 wt% T g <0℃ polymer inner shell, c. 5-50 wt% T g >0℃ polymer housing, The ratio of the surface area of the emulsifier to the surface area of the core-shell particles, based on the core-shell particles as synthesized and without further processing, is less than 1.5×10 -4 g / m 2 , The radius of the core-shell particles is determined by light scattering on latex using a NICOMP380 dynamic light scattering instrument, and T g Determined by DSC according to Standard ISO 11357-2 (2013) and Standard ISO 11357-3 (2013).
2. The core-shell particle of claim 1, wherein the core-shell particle comprises 55-80 wt % of T g Polymer inner shell <0°C.
3. The core-shell particle according to claim 1 or 2, wherein the core-shell particle comprises 10-20 wt % of T g >0℃ polymer housing.
4. The core-shell particle of claim 1, wherein the hard core polymer grade comprises at least 50 wt% of monomer units selected from the group consisting of methacrylate units, acrylate units, styrene units, and mixtures thereof.
5. The core-shell particle of claim 1 or 4, wherein the polymer inner shell comprises at least 50 wt% of monomer units selected from the group consisting of alkyl acrylates, dienes, styrenes and mixtures thereof.
6. The core-shell particle of claim 1 or 4, wherein the polymer shell comprises at least 50 wt% of monomer units selected from the group consisting of methacrylate units, acrylate units, styrene units, and mixtures thereof.
7. A polymer impact-modified composition, comprising: a.) 30-99 wt. % of at least one polymer resin as a matrix, and b) 1 to 70% by weight of the core-shell particles according to any one of claims 1 to 6.
8. The impact-modified composition of claim 7, wherein the polymer impact-modified composition comprises 10-60 wt% of the core-shell particles of any one of claims 1-6.
9. The impact-modified composition of claim 7, wherein the polymer impact-modified composition comprises 20-50 wt% of the core-shell particles of any one of claims 1-6.
10. An article comprising the impact-modified composition of any one of claims 7-9.
11. The article of claim 10, wherein the article is a multi-layer article, wherein at least one layer comprises the impact-modified composition of any one of claims 7-9.
Citation Information
Patent Citations
Impact-resistant molding material having an improved characteristics profile
US20170298217A1
Graft polymers of rubber for reinforcing plastics
US3661994A
Composite interpolymer and low haze impact resistant thermoplastic compositions thereof
US3843753A
Machine for balling twine
US443103A
Sequentially produced multilayer acrylic resin composition
US4521568A